1996
DOI: 10.1159/000117218
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Mortality in Patients with Early-Onset Alzheimer’s Disease

Abstract: In a population-based study of 198 patients with probable early-onset Alzheimer’s disease (AD), we studied the occurrence of extrapyramidal signs (tremors and rigidity), myoclonus, psychosis and seizures, as well as their predictive value for mortality. The presence of tremors was significantly associated with the presence of rigidity. The occurrence of myoclonus was significantly associated with the occurrence of seizures. Psychosis and seizures in AD patients were not associated with mortality. The occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
50
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 0 publications
2
50
1
1
Order By: Relevance
“…12 In this study we noted associations between tremor and functional decline and tremor and mortality, but the relationships did not reach significance in the adjusted models. Tremor in the present study was mostly associated with higher risk for cognitive decline.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…12 In this study we noted associations between tremor and functional decline and tremor and mortality, but the relationships did not reach significance in the adjusted models. Tremor in the present study was mostly associated with higher risk for cognitive decline.…”
contrasting
confidence: 56%
“…5 In addition, information about presence of motor signs in AD is important because they may predict cognitive [6][7][8][9] and functional 2,10 decline, institutionalization, 2,10 and death. [10][11][12][13][14][15][16] However, some reports failed to detect significant associations for cognition, 2,[17][18][19] function, 17,18,20 institutionalization, 20 or mortality. 21,22 Many factors contribute to the variability in reported associations between motor signs and AD outcomes.…”
mentioning
confidence: 99%
“…One study found that nursing home residents who later died had displayed more verbal agitation than those who survived during the same follow-up period (t ¼ 2.03, effect size 0.51) (Allen et al, 2005); however, another study reported that the association between mortality and agitation in dementia disappeared on multivariate analysis (Bowen et al, 1996). Likewise, some investigations have demonstrated an association between psychosis of dementia and increased mortality (Wilson et al, 2006), whereas other researchers have not found such a relationship (Samson et al, 1996;Rosen and Zubenko, 1991).…”
mentioning
confidence: 99%
“…5 In addition, information about presence of motor signs in AD is important because they may predict cognitive [6][7][8][9] and functional 2,10 decline, institutionalization, 2,10 and death. [10][11][12][13][14][15][16] However, some reports failed to detect significant associations for cognition, 2,[17][18][19] function, 17,18,20 institutionalization, 20 or mortality. 21,22 Many factors contribute to the variability in reported associations between motor signs and AD outcomes.…”
mentioning
confidence: 99%